Serum Osteocalcin and Serum Osteopontin Levels in Osteoporotic Postmenopausal Women with and without Vertebral Fractures - Mohammed, Nawar S.; Turki, Kisma M.; Munshed, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Osteoporosis is a progressive systemic skeletal disorder characterized by low bone mass and micro-architectural deterioration of bone tissue spatially in postmenopausal women and its major complication fractures.Objective: The aim of this study was to find out the significance of serum OC and serum OPN levels with the incidence of osteoporosis and its major complication (fractures).Patients and Methods: Eighty-five postmenopausal women (PMW) whose ages were fifty years and over categorized into three groups: osteoporosis PMW without VFs (n=30), osteoporosis PMW with VFs (n=28), and healthy PMW (n=27). Sera samples were analyzed for alkaline phosphatase, calcium and phosphorous by using spectrophotometric kit. Serum OC and serum OPN levels were measured by ELISA kits.Results: Bone Mineral Density (BMD) and T-score were significantly lower in osteoporotic PMW with and without VFs as compared with healthy PMW (p=0.0001, p=0.0001, respectively). Serum OC levels and serum OPN levels were elevated significantly in osteoporotic PMW with and without VFs as compared with healthy PMW (p=0.0001, p=0.0001, respectively), the levels of serum OC and OPN showed a significant positive correlation with age in osteoporotic PMW. There is a significant positive correlation between serum OC levels and serum OPN levels in osteoporotic PMW and non-significant correlation was found in healthy PMW.Conclusion: The levels of serum OC and OPN can be used as a biochemical indicator in the diagnosis of postmenopausal osteoporotic women